High Doses of Dexamethasone Improved Hemoglobin Levels Lowered by Corona Virus in COVID-19 Infected Patients: Dexamethasone and Hemoglobin in COVID-19 - Chaudhry, Zunnera Rashid; Shakir, Sabeen; Rasheed, Sana; Rashid, Erum; Lodhi, Hifza Noor; Shakeel, Naima (Pakistan Journal of Health Sciences, 2024)
Corona virus an infectious disease caused by SARS–CoV-2 virus that lower hemoglobin level leading to worsening of the conditions. The respiratory symptoms are treated by steroids and patients are rapidly recovered. Objective: To study the effect of high and low doses of dexamethasone on hemoglobin level in COVID-19 infected patients. Methods: This experimental study was carried out in Rawal Institute of Health Sciences, Islamabad and Pakistan Institute of Medical Sciences, Islamabad between May 2021 to Sep 2021 on 100 adult male and female of COVID-19 patients having blood hemoglobin level < 10 g/dl. For different doses of dexamethasone patients were divided into two groups of 50 patients in each group. Blood samples were taken on day 01 and day 15 for hemoglobin analysis. Mean and standard deviation of both groups was calculated and p-value of < 0.05 was considered significant. Results: At the time of admission 74% of the patients had a cough, 89% of the patients presented with fever, 98% had increased heart rate whereas 100% of the patients presented with the complaint of fatigue. Mean Hemoglobin (Hb) levels of both groups were compared on day 01 and day 15 respectively. The comparison of Hb levels showed a significant difference on day 15, there was a marked increase in Hb levels in the group which was taking 12mg/day of dexamethasone as compared to the group which was taking 6mg/day of dexamethasone (P-value <0.05). Conclusions: Administration of high doses of Dexamethasone caused a pronounced increase in hemoglobin levels in COVID-19 patients